2020
DOI: 10.1101/2020.03.18.998070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RRBP1 rewires cisplatin resistance in Oral Squamous Cell Carcinoma by regulating YAP-1

Abstract: 30Cisplatin-based chemotherapy still remains as one of the primary treatment modalities for 31 OSCC. Several OSCC patients experience relapse owing to development of chemoresistance. To 32 identify key resistance triggering molecules, we performed global proteomic profiling of human 33 OSCC lines presenting with sensitive, early and late cisplatin resistance patterns. From the 34 proteomic profiling study, human RRBP1 was identified to be upregulated in both early and late 35 cisplatin-resistant cells with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…We found that during the period of treatment responsiveness, our genes change their expression level from low to high again, which is the same as the prior treatment. Other studies have also determined the involvement of these genes in resistance generation, for example, SERPINE1 is upregulated in cisplatin-resistant oral cancer cell lines (SCC9, SCC4, and H357) ( 68 ) and paclitaxel-resistant breast cancer ( 44 ). In the context of therapeutic potential, SERPINE1 has been identified as a potential therapeutic target, as it acts as a pro-proliferative oncogenic factor ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that during the period of treatment responsiveness, our genes change their expression level from low to high again, which is the same as the prior treatment. Other studies have also determined the involvement of these genes in resistance generation, for example, SERPINE1 is upregulated in cisplatin-resistant oral cancer cell lines (SCC9, SCC4, and H357) ( 68 ) and paclitaxel-resistant breast cancer ( 44 ). In the context of therapeutic potential, SERPINE1 has been identified as a potential therapeutic target, as it acts as a pro-proliferative oncogenic factor ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of therapeutic potential, SERPINE1 has been identified as a potential therapeutic target, as it acts as a pro-proliferative oncogenic factor ( 69 ). PLAU is found to be upregulated in cisplatin-resistant oral cancer cell lines ( 68 ). Both PLAU and SERPINE1 were found to be highly expressed in breast cancer patients with adjuvant endocrine therapy and related to shorter disease-free survival and OS ( 70 ).…”
Section: Discussionmentioning
confidence: 99%